2012
DOI: 10.1097/mcd.0b013e328358243c
|View full text |Cite
|
Sign up to set email alerts
|

VATER/VACTERL association

Abstract: The VATER/VACTERL association is typically defined by the presence of at least three of the following congenital malformations: vertebral anomalies, anal atresia, cardiac malformations, tracheo-esophageal fistula, renal anomalies, and limb abnormalities. The identification of 14 twin pairs with an initial diagnosis of VATER/VACTERL association at our clinical centers led to the performance of a classical twin study. This involved a thorough evaluation of these 14 twin pairs and a further 55 twin pairs identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Recent twin studies support a low proportion of genetic abnormalities found in VACTERL patients [33], [34].…”
Section: Discussionmentioning
confidence: 93%
“…Recent twin studies support a low proportion of genetic abnormalities found in VACTERL patients [33], [34].…”
Section: Discussionmentioning
confidence: 93%
“…Reports where zygosity was not reported (for example, the author did not comment on whether the twins were thought to be monozygotic or dizygotic) were excluded. Because twin studies on OAVS and VACTERL that relied on exhaustive literature searches had been previously published (Bartels et al, 2012;Wieczorek et al, 2007), we relied on references from these studies in addition to performing PubMed searches using the search terms in Table 3 to capture relevant literature that had been published after 2007 and 2012, respectively, for these two conditions. Our literature search terms are summarized in Table 3.…”
Section: Determination Of Minimum Diagnostic Criteria and Literaturmentioning
confidence: 99%
“…but this has only been tested statistically for VACTERL (Bartels et al, 2012) and OAVS (Wieczorek et al, 2007). Given the retrospective nature of the reports included in our analysis, many providing only partial data on zygosity, we chose to analyze zygosity directly from data provided in the reports and indirectly using Weinberg's differential rule (Fellman & Eriksson, 2006), expecting the latter to be more accurate as it is free of reporting bias.…”
Section: Zygositymentioning
confidence: 99%
See 2 more Smart Citations